Chemical characteristics, antioxidant capacities and hepatoprotection of polysaccharides from pomegranate peel. (15th December 2018) - Zhai, Xichuan; Zhu, Caiping; Zhang, Yang; Sun, Jingru; Alim, Aamina; Yang, Xingbin
Highlights: A novel heteropolysaccharide was extracted from pomegranate peel. PPP has good antioxidant activity in vitro . PPP had a prominent preventive effect against CCl4 -induced liver injury. Pathological test confirmed PPP could alleviate CCl4 -caused histological lesion. PPP is a good natural source for dietary supplement and therapeutic application. Abstract: This proposed work aimed to investigate the chemical characteristic, antioxidant capacities and hepatoprotection effect of pomegranate peel polysaccharides (PPP) on CCl4 -induced oxidative damage in mice. PPP was identified as the acidic heteropolysaccharides by HPLC methods. In vitro test showed that PPP had excellent reducing power and scavenging effects against free radicals. Administration of PPP (50, 100 and 200 mg/kg·bw) in mice before the injection of CCl4 could observably antagonize the increased serum alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase and hepatic malonaldehyde level in CCl4 -induced mice, especially administrated with 200 mg/kg·bw of PPP. Hepatic enzymatic activities of total superoxide dismutase, glutathione peroxidase, catalase and non-enzymatic activity of glutathione were markedly increased at high dosage of PPP, respectively. In addition, histopathological observation of liver further proved these biochemical characteristics. Therefore, it can be concluded that PPP exhibits strong protective effects against CCl4 -induced liver injury in mice.